Association of dust exposure with anxiety and depression in the occupational population: The important role of sleep duration - Zhuoheng Shen; Yue Sun; Yang Li; Qi Zhang; Yifei Liu; Jiyan Han; Jiafei Yang; Jiangping Li; Zhiyun Ha; Yaowen Yang; Zhihong Liu; Suzhen Guan; et al. (BMC Public Health)
Abstract Background Mental health issues, particularly anxiety and depression, are increasingly prevalent among the occupational population. Environmental factors, such as dust exposure, may contribute to the worsening of these symptoms. While previous studies have examined the association between dust exposure and mental health, the moderating effect of sleep duration on this link in occupational settings remains under-explored. Methods This study was conducted from July to October 2023 at The Fifth People's Hospital of Ningxia and recruited dust-expose d occupational workers from different coal enterprises. After a series of screening 1274 valid subjects were finally included. Binary logistic regression was used to explore the association of dust exposure with anxiety and depression. Generalized additive models (GAM) were constructed to explore the nonlinear relationships between dust exposure duration, sleep duration, and mental health outcomes. Mediating variable contributions were isolated using the Karlson-Holm-Breen (KHB) method and mediated effects models were fitted. Results The prevalence of anxiety and depression was found to be 6.44% and 4.24%, respectively. Dust exposure duration was positively associated with both anxiety and depression, while stratification by monthly income level had no significant effect. The contribution of sleep duration to the indirect effect accounted for 21.76% and 43.54% of the total effect of dust exposure duration on anxiety and depression scores, respectively. A nonlinear relationship was observed between dust exposure duration, sleep duration, and the scores of anxiety and depression. In the mediation analysis, shorter sleep duration explained 12.87% of the association between dust exposure duration and anxiety scores. Conclusions Dust exposure duration was associated with anxiety and depression, with a nonlinear relationship between them. Changes in sleep duration may effectively influence mental health problems in occupationally dust-exposed populations.